2019
DOI: 10.3390/diseases7010023
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Ionizing Radiation on Echinococcus granulosus Hydatid Cyst

Abstract: Background: Heavy ion radiation has more advantages than traditional radiation therapy in the treatment of cancer, mainly because of its superior biological effects. However, there is currently no reliable evidence that heavy ion radiation can induce cell death in hydatid cysts at the cellular and molecular level. In addition, we believe heavy ion therapy could be a potential alternative approach for the treatment of hydatid cysts. Methodology/Principal Finding: The hydatid cysts and protoscolices were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Recently, few studies have been available to focus on utilizing irradiation for treating such disease. In an earlier study, Zhao et al indicated that heavy-ion radiation could induce the extinction of hydatid cysts in vitro [ 23 ]. However, rarely studies have been focused on the roles of radiation in hydatid disease under in vivo conditions [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, few studies have been available to focus on utilizing irradiation for treating such disease. In an earlier study, Zhao et al indicated that heavy-ion radiation could induce the extinction of hydatid cysts in vitro [ 23 ]. However, rarely studies have been focused on the roles of radiation in hydatid disease under in vivo conditions [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…23,24 These protoscoleces have been widely used as an in vitro and in vivo study model to investigate the scolicidal effect and immunomodulatory properties of many chemical and/or natural molecules. [25][26][27][28][29][30][31][32][33][34][35] They have been also used to investigate the effect of radiation for therapeutic use or preventing echinococcosis recurrence after surgical removal of hydatid cysts [36][37][38][39][40][41] and to assess the potential of many molecules as novel vaccine for preventing infection. 9,16,17 Our study was conducted to investigate the immunoprotective effect against experimental murine echinococcosis by using gamma rays irradiated protoscoleces.…”
Section: Introductionmentioning
confidence: 99%
“…These protoscoleces have been widely used as an in vitro and in vivo study model to investigate the scolicidal effect and immunomodulatory properties of many chemical and/or natural molecules 25–35 . They have been also used to investigate the effect of radiation for therapeutic use or preventing echinococcosis recurrence after surgical removal of hydatid cysts 36–41 and to assess the potential of many molecules as novel vaccine for preventing infection 9,16,17 …”
Section: Introductionmentioning
confidence: 99%
“…So far, various mechanical methods and chemical agents have been tested in order to prevent the formation of secondary hydatidosis. The antiparasitic ef-fects of direct electric current [1], magnetic field [2], xray [3], UV light [4], gamma irradiation [5], ultrasound [6,7], nanoparticles [8], hypotonic saline [9], silver nitrate [10], vinegar [11] and various herbal extracts or essential oils have been evaluated on protoscoleces to certain extents [12][13][14].…”
Section: Introductionmentioning
confidence: 99%